In silico investigation of black tea components on α-amylase, α-glucosidase and lipase - Satabdee Mohapatra, Alisha Prasad, Farhan Haque, Sonali Ray, Bratati De, Sirsendu Sekhar Ray (Journal of Applied Pharmaceutical Science, 2015)
Black tea is one of the most widely consumed beverages in the world and traditionally known for its antidiabetic and antiobesity property. However, the underlying mechanisms of these properties are not studied widely. In this work, we hypothesize that the reason could be because of the inhibition of gut enzymes by the tea derived phytochemicals. Molecular docking was used to explore the efficacy of tea components to inhibit the key enzymes related with Type II diabetes and obesity; α-glucosidase, α-amylase and lipase. Autodock4.2 molecular docking software that applies Lamarckian Genetic Algorithm was used. The ligand structures were retrieved from PubChem and KNApSAcK-3D database. PreADMET web server was used for Toxicity and ADME predictions. Based on this analysis, it has been found that 8-c-ascorbyl-(-)-epigallocatechin, rutin and orientin could be the putative molecules for amelioration of post-prandial hyperglycaemia whereas 8-c-ascorbyl-(-)-epigallocatechin,8-c-ascorbyl epigallocatechin 3-o-gallate and schaftoside could be used to reduce fat absorption in obese persons. It can be concluded that these phytochemicals or their derivatives can be used for further in-vitro and in-vivo studies to design valuable drugs.
Keywords: Blacktea, Diabetes, Obesity, Molecular Docking, PreADMET.